2022
DOI: 10.1093/mnras/stac2108
|View full text |Cite
|
Sign up to set email alerts
|

Dust grain size evolution in local galaxies: a comparison between observations and simulations

Abstract: The evolution of the dust grain size distribution has been studied in recent years with great detail in cosmological hydrodynamical simulations taking into account all the channels under which dust evolves in the interstellar medium. We present a systematic analysis of the observed spectral energy distribution of a large sample of galaxies in the local Universe in order to derive not only the total dust masses but also the relative mass fraction between small and large dust grains (DS/DL). Simulations reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 159 publications
0
5
0
Order By: Relevance
“…Vis et al 2017a)11 . Comparisons with the literature require to pay attention to derivation method of the involved quantities and this is particularly important for the dust mass whose values are strongly dependent on adopted SED fitting and dust model (see, e.g.,Relaño et al 2022). However, De Vis et al (2019) found that dust masses used in De Vis et al (2017a) derived with MAGPHYS (da Cunha et al 2008) and the DustPedia ones (see Sect.…”
mentioning
confidence: 95%
“…Vis et al 2017a)11 . Comparisons with the literature require to pay attention to derivation method of the involved quantities and this is particularly important for the dust mass whose values are strongly dependent on adopted SED fitting and dust model (see, e.g.,Relaño et al 2022). However, De Vis et al (2019) found that dust masses used in De Vis et al (2017a) derived with MAGPHYS (da Cunha et al 2008) and the DustPedia ones (see Sect.…”
mentioning
confidence: 95%
“…The models are also applied to nearby galaxies in order to extract the information on dust properties (e.g. Li & Draine 2002; Draine & Li ★ E-mail: hirashita@asiaa.sinica.edu.tw 2007; Galliano et al 2018;Relaño et al 2020Relaño et al , 2022. All these models are useful not only to understand dust extinction and emission but also to infer the dust composition and grain size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Observationally, the determination of the relative abundance of small and large grains may be estimated with SED fitting. This estimate has been done for a sample of local galaxies in two recent works by Relaño et al (2020) and Relaño et al (2022), whose results are shown in Fig. 9 together with our model predictions.…”
Section: Grain Sizesmentioning
confidence: 83%
“…We caution the reader about this comparison. Indeed, while in our two size approximation the transition from small to large grains occurs at 0.03 𝜇m, it occurs at 0.015 𝜇m in the model 16 adopted by Relaño et al (2020) and Relaño et al (2022). Moreover, they assume carbonaceous properties for small grains, while we also consider small grains to have a silicate composition.…”
Section: Grain Sizesmentioning
confidence: 90%
See 1 more Smart Citation